Psychiatric Manifestations in a Child with Periventricular Leukomalacia: A Case Report and Literature Review - Parikh, Dr. Parinda; Dadem, Ananya Reddy; Wubuli, Dilinuer; Wang, Eric; Singh, Shaurya Kumar; Suthar, Himani J; Sood, Kanuja; Chandra-Kaushik, Arushi; Narravula, Rithika; Manepalli, Sahia; Witriol, Henny; Oza, Dr. Mina (International Journal of Innovative Research in Medical Science, 2025)
Background and Objectives: Periventricular Leukomalacia (PVL) is a type of brain injury that involves damage to the white matter around the brain’s fluid-filled ventricles. PVL is more commonly reported in premature infants, and existing studies have associated it with neurodevelopmental sequelae, but its role in behavioral disorders and mood dysregulation in children has not yet been elucidated. This research article aims to evaluate the psychiatric effects of PVL using both pre-existing literature and a clinical case study. Methods: A qualitative investigation of English-language literature published after the year 2000 was performed in PubMed and Google Scholar using the following keywords: periventricular leukomalacia, behavioral disorder, attention deficit and hyperactivity disorder (ADHD), anxiety disorders, and disruptive mood dysregulation disorder. No preference was given. All available literature, including case reports, extensive cohort studies, and mechanistic papers providing insight into PVL pathophysiology, were reviewed, analyzed, and collected. Case Presentation: We report a rarely documented case of a 10-year-old female with PVL presenting with frequent outbursts of aggressive behavior, persistent irritability, refusal to sleep, enduring anxiety, depressed mood, and suicidal ideation. Collateral history reveals that symptoms have been prevalent for a significant period and have progressively worsened. Results and Conclusion: This case illuminates the possibilities of pediatric patients with PVL developing mood and behavioral disorders, emphasizing the need for a multidisciplinary assessment and long-term psychiatric monitoring.